Empowering local communities engagement: Rural tourism and business innovation for SDGs desa - Eman Sulaiman; Gian Fitralisma; M. Anissul Fata; Rusto Nawawi (Goodwood Publishing, 2023)
Purpose: This study investigates the role of social entrepreneurship and business innovation in empowering local communities for rural tourism development within the framework of sustainable development goals (SDGs). Research methodology: A comprehensive review of the existing literature on social entrepreneurship, business innovation, and rural tourism development is conducted. The study also involved qualitative interviews with key stakeholders and community members in the selected villages, followed by thematic analysis of the data. Results: The findings reveal that Social entrepreneurship plays a crucial role in fostering community engagement, promoting social inclusivity, and creating sustainable tourism initiatives. On the other hand, business innovation enables local communities to differentiate themselves, enhance visitor experiences, and improve the overall competitiveness of rural tourism destinations. Limitations: This study acknowledges certain limitations, including the selection of a limited number of case study villages and potential bias in qualitative interviews. Further research is needed to explore the generalizability of the findings across different contexts. Contribution: This study contributes to the understanding of the synergistic relationship among social entrepreneurship, business innovation, and rural tourism development. These findings provide insights for policymakers, community leaders, and practitioners in designing effective strategies to empower local communities and promote sustainable tourism within the SDGs Desa framework. Novelty: The novelty of this study lies in its comprehensive examination of the combined influence of social entrepreneurship and business innovation on rural tourism development in the context of sustainable development goals (SDGs Desa). This highlights the potential of these concepts to drive positive change and create inclusive and resilient rural tourism destinations.